Engineered Nanostructural Films and Materials 1999
DOI: 10.1117/12.351251
|View full text |Cite
|
Sign up to set email alerts
|

Moisture adsorption effects in biaxial and chiral optical thin film coatings

Abstract: Thin film form birefringence depends on the shape or bunching of nanostructural columns and on the difference in the refractive indices of the columns and the surrounding voids. When moisture from the atmosphere enters the nanostructure the linear form birefringence may decrease by a large amount, of the order of 50%. However, current data refers to tilted-columnar films. We report here on moisture penetration effects in films fabricated by serial bideposition and engineered for large linear form birefringence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…However, this index contrast for PTFs is only about 28% greater than that of the template films, thus suggesting that the index contrast alone cannot explain the entire effect. It has previously been noted that water ( ) can infiltrate porous films and condense within them [33], possibly leading to unwanted shifts in the optical characteristics of porous thin film media. The effect of water infiltration can be quite dramatic and has been exploited to produce GLAD-based capacitive humidity sensors [34], [35].…”
Section: Optical Rotation Measurementsmentioning
confidence: 99%
“…However, this index contrast for PTFs is only about 28% greater than that of the template films, thus suggesting that the index contrast alone cannot explain the entire effect. It has previously been noted that water ( ) can infiltrate porous films and condense within them [33], possibly leading to unwanted shifts in the optical characteristics of porous thin film media. The effect of water infiltration can be quite dramatic and has been exploited to produce GLAD-based capacitive humidity sensors [34], [35].…”
Section: Optical Rotation Measurementsmentioning
confidence: 99%
“…Adsorption of toluene on the anisotropic TiO 2 film causes the refractive index of the film to increase due to the void volume ( n ≈ 1) being displaced by toluene ( n 800nm = 1.49), while the anisotropy of the film decreases because the refractive index contrast between the columns ( n columns ) and the surroundings ( n surroundings ) is reduced . Both of these changes are directly observed through specific Mueller matrix elements.…”
mentioning
confidence: 99%
“…In particular, theoretical research has shown that the Bragg regime of a chiral STF must shift accordingly, thereby providing a measure of the fluid concentration [37]. Qualitative support for this finding is provided by experiments on wet and dry chiral STFs [39].…”
Section: Fluid Sensorsmentioning
confidence: 50%